Non-enzymatic electrochemical detection of cholesterol using β-cyclodextrin functionalized graphene - Agnihotri, Nidhi; Chowdhury, Ankan Dutta; De, Amitabha (Biosensors & bioelectronics, 2015)
A non-enzymatic approach towards cholesterol detection is presented here, exploiting the electrochemical non-enzymatic route of sensing which has a distinct advantage over other conventional enzymatic processes. Chemically converted Graphene modified with β-CD, being hydrophilic, electroactive and high surface area material, provides a platform for the electrochemical detection of cholesterol using Methylene Blue as redox indicator. Methylene Blue (MB) forms an inclusion complex with Grp-β-CD and emerges as a cholesterol sensing matrix. MB molecule is replaced by cholesterol molecule and moves out in the buffer solution, hence, detected electrochemically using Differential Pulse Voltammetric (DPV) technique. The sensing matrix is characterised using FT-IR and Raman spectroscopy. Transmission Electron Microscopy is carried out to study the morphology of functionalized graphene sheets. [Display omitted] •Non-enzymatic route of cholesterol sensing, using MB as redox indicator.•Better solubility of Grp-β-CD-MB (sensing probe) due to hydrophilic interactions.•Entrapment of cholesterol inside Grp-β-CD-MB cavity, forming an inclusion complex.•Cholesterol detection using DPV in a wide range of 1–100µM and high sensitivity.